(untitled) (Baghdad Science Journal, 2014)
A total of 437 individuals of Turbellarin Platyhelminthes were sorted from benthic samples collected monthly for a period of seven months( April to November 2013 ) from AL-Dalmage lake, a part of middle section for main outfall drain south of Baghdad. They were identified as Gyratrix hermaphroditus, Stenostomum leucops ,Stenostomum unicolar and Stenostomum bryophilum ,The relative abundance of worms decreased during hot season which (May to September) ,where they start rising again. The species were studied alive , the identification criteria were illustrated by photos. G. hermaphroditus was the most abundant species among the four species.